Managing economic climate security: theoretical and applied aspects - E. N. Yakovleva (Вестник университета, 2022)
The article proposes to consider climate security as an important factor in the sustainable development of the economy. The problems of climate risk management have been identified. Based on a literature review, a system of national climate regulation objectives have been proposed and logically justified. The main stages of their achievement have been presented. The need for a project-based approach to climate regulation has been justified. The idea of a national project at state level and three federal projects as part of it has been proposed. The author’s model for managing the country’s climate security has been presented. The standard plan for the implementation of this model at the regional level has been developed. The results can be used in national strategic management of country climate security and its constituent entities.